Influence of high temperature and drought stress at jointing stage on crop physiological responses and growth in summer maize plants (Zea mays L.) - Fan, Xiaodong; Hu, Xiaotao; Ma, Yuxin; Pang, Yaoyue; Sun, Jun; Hou, Panpan (Frontiers in Plant Physiology, 2024)
The combination of low precipitation and high temperature stresses at jointing stage can severely threaten maize production. However, to date, few studies have been conducted on the effects of combined stress on maize plants expression at jointing stage. In the current research, plant growth, root morphology, and yield components were determined after exposure to the single and combined stress of high temperature and drought stress. Leaf gas exchange, malondialdehyde (MDA) content and antioxidant enzymes activities were conducted to identify potential mechanisms of stress responses. The single stress of high temperature and drought significantly reduced the biomass of various organs and the total aboveground biomass, which reduced the yield of maize plants. High temperature substantially decreased aboveground biomass and yield under mild and severe water stress, which indicated that the inhibitory effects of combined stress were more significant than that of high temperature or drought individually.High temperature exacerbated the negative impacts of water stress on plants growth and yield as shown by the reduced leaf photosynthetic rate (P n ), probably related to the increasing MDA content. Leaf-level water use efficiency (WUE) was enhanced as the reduction in leaf transpiration (T r ) was greater than the decrease in leaf photosynthesis under high temperature, even for those plants were suffering water stress. High temperature, drought stress and their combination all greatly increased the activities of superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT), but were ineffective in mitigating oxidative damage. The MDA content and antioxidant enzymes activities showed an increasing trend following 12 days of combined stress. This substantiated the irreversible damage induced by combination of high temperature and desiccation stresses. The combined stress optimized roots length, root volume, root surface area, and thinned the average root diameter, which improved the adaptation of maize to high temperature, drought and combined stress. This study has provided meaningful references for improved understanding the impacts of drought, high temperature, and concurrent events on the physiology and growth of maize plants during the jointing period.